Culturable bacteria resistant to oxytetracycline during the vermicomposting of bovine excreta - Uribe-Lorío, Lorena (2023)
Introduction: Bacteria with resistance genes to the antibiotic oxytetracycline have been detected in dairy cow manure worldwide, however, it is common a practice to use this manure as fertilizer. Vermicomposting can reduce the problem, but this subject has not been evaluated in Costa Rica. Objective: To analyze the presence of bacteria resistant to oxytetracycline during vermicomposting in a Costa Rican dairy farm. Methods: We inoculated broths supplemented with oxytetracycline from fresh manure, precomposted manure, vermicompost and "compost teas" with and without molasses. We prepared “compost teas” with and without molasses from this sample. We extracted DNA from these liquid cultures and mass-sequenced the 16S ribosomal amplicon. Results: We classified 105 292 sequences in 58 amplicon sequence variants from broths supplemented with oxytetracycline, most of them identified as Proteobacteria, Bacteroidetes and Firmicutes. Fresh manure had the most resistant bacteria (32), followed by the “teas” without and with molasses. Precomposting and vermicomposting decreased the number and type of resistant bacteria. However, preparation of the teas caused the multiplication of bacterial genera recognized for their ability to accumulate resistance determinants. Conclusion: Precomposting and vermicomposting decreased the number and type of resistant bacteria.